Pelaksanaan Penempatan Tenaga Kerja Tempatan Sesuai Peraturan Daerah Kabupaten Kampar Nomor 5 Tahun 2009 tentang Penempatan Tenaga Kerja pada PT. Flora Wahana Tirta - Rino Rinaldo (Jurnal Hukum Respublica, 2020)
Employment Development has a broad scope and is cross-sectoral in nature,then Manpower Development is an overall effort in all sectors and regions aimed at expanding employment opportunities.In the framework of implementing Presidential Decree No. 4 of 1980 concerning mandatory reporting of job vacancies, efforts should be made to the maximum extent possible to fill vacancies available by local (local) workers.The problem discussed in this study is the Implementation of Placement of Workers in accordance with the Local Regulations Kampar Regency Number 5 of 2009 concerning the Placement of Workers at PT. Flora Wahana Tirta.This type of research is Sociological legal research which is more directed at research that addresses the enactment of positive law, the enactment of positive law on people's lives and also the influence of non-legal factors on the formation of positive legal provisions.Muhammad Hasnan Husainu conducted a study of this research, with the research title Implementation of the Regional Regulation Policy of Kampar Regency No. 5 of 2009 concerning the Placement of Local Workers (Case Study of PT. Ramajaya Pramukti).Differences in studies conducted by Muhammad Hasnan Husainu are in the research location.Location of research conducted by Muhammad Hasnan Husainu at PT. Ramajaya Pramukti, while the research location in this article is PT. Flora Wahana Tirta.